DESIGN OF COFFEE VISUAL IDENTITY AS A PROMOTIONAL MEDIA (Arty: Jurnal Seni Rupa, 2021)
For a new coffeeshops, Tjilik Coffee has have a basic problems such as the absence of an identity that can be a characteristic of coffeeshops and problems regarding the types of promotions and effective media used as promotional media. The design of visual identity and its application in promotional media is a solution that is considered to be able to overcome the problem of Tjilik Coffee and can form a characteristic that can increase the selling value of the coffee shop in the eyes of the community. In addition, visual identity design can also be a medium to introduce Tjilik Coffee's identity with a wider reach. The visual identity design is determined using the classic main theme and is divided into several printed and online media with several stages including preliminary, pre-production, production, and post-production. In addition, the printing techniques used to print promotional media include digital printing, translucent printing/screen printing, and embroidery. Visual identity design which is then applied to promotional media produces works in the form of logos, stationery sets (business cards, envelopes with letterhead, folders, notebooks), brochures, posters, packaging (ice cups, hot cups, coffee bean packaging), uniforms, vehicles , booths, merchandise (t-shirts, totebags, patches, lighters, keychains), and digital content. Some of the promotional media produced are media that are considered needed by management in improving the name of Tjilik Coffee because they have persuasive, informative, and media support properties. With the creating a visual identity, hoped can improve and help the name of Tjilik Coffee in the visual field as a coffeeshop that has distinctive characteristics and is expected to expand the targeted market segmentation optimally, and can provide a good image in the public.